Emerging presence of Pasteurella bettyae in a woman’s genital tract - Gómez-Camarasa, Cristina (2020)
A clinical case is described where the presence of Pasteurella bettyae in an endocervical exudate in a 45-year-old patient is demonstrated, but it cannot be assured as the sole cause of the infection. Its presence may indicate a colonization, although this microorganism is not recognized as part of the human microbiota. Despite its rarity, thanks to the Maldi-Tof test applied to colonies that grow in culture media, it is possible to know the infrequent presence of this type of microorganism.